PENGARUH PENGETAHUAN PERPAJAKAN, KETEGASAN SANKSI PAJAK, TAX AMNESTY, LINGKUNGAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (Studi Kasus di Kantor Pelayanan Pajak Pratama Jayapura) - Maria Cristine Andiko; Meinarni Asnawi; Bill J.C Pangayow (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2018)
This study aims to determine whether the influence of tax knowledge affect taxpayer compliance. The Influence of Tax Knowledge, Assertiveness of Tax Sanctions, Tax Amnesty, Taxpayer Environment which become independent variable in this research. While the dependent variable is taxpayer compliance.This research uses qualitative approach with its research population that isTaxpayer in KPP Pratama Kota Jayapura. Primary data collection using questionnaire. The sampling technique uses convenience sampling. Data analysis in this research use multiple linear regression analysis. The results of this study indicate that there is a positive influence between the influence of taxation knowledge on taxpayer compliance, the positive influence between the firmness of tax sanctions on taxpayer compliance, the positive influence between tax amnesty on taxpayer compliance, no taxpayer environment influence on taxpayer compliance, taxation, assertion of tax sanction, tax amnesty, taxpayer environment simultaneously have a significant effect on taxpayercompliance in KPP Pratama jayapura